Stable, Porous, and bulky Particles with High External Surface and Large Pore Volume from Self-assembly of Zeolite Nanocrystals with Cationic Polymer - Song, Jiangwei; Ren, Limin; Yin, Chengyang; Ji, Yanyan; Wu, Zhifeng; Li, Jixue; Xiao, Feng-Shou (Journal of physical chemistry. C, 2008)
Stable, porous, and bulky beta zeolite particles (bulky-beta) with high external surface area and large pore volume were fabricated from the self-assembly of beta nanocrystals with cationic polymers under hydrothermal condition, followed by filtration and calcination. The samples were characterized using powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, N2 isotherm, and thermogravimetric analysis−differential thermal analysis. The results show that bulky-beta contains disordered mesopores, and its mesoporous walls are connected by beta nanocrystals with each other. The formation of mesoporosity in bulky-beta is proposed by the use of mesoscale organic template of cationic polymer in the synthesis. The bulky particles of bulky-beta are mechanically stable even if subject to an ultrasonic treatment for 15 min. This is very useful for the separation of zeolite particles from a slurry system via a filtration route. Very interestingly, these particles show almost the same catalytic activity and a very high yield of solid product, compared with nanocrystals of beta zeolite. This method may provide a novel route for the synthesis of catalytically active zeolites, enabling good mass transport as stable and active catalysts in potential industrial applications.